ANALISIS KETERTARIKAN MAHASISWA DEPARTEMEN SEJARAH FIS UNP TERHADAP SISTEM BELAJAR DARING - Nazar, Putra Burhanudin; Karima, Elfa Michellia (Puteri Hijau : Jurnal Pendidikan Sejarah, 2023)
This research was raised due to the COVID-19 pandemic that hit the world. This pandemic certainly has an impact on the world of education. The government overcame the spread of COVID-19 by moving all face-to-face activities online. Padang State University also appealed to students, teaching staff, and staff to do work at home (online). In the online learning system, researchers saw that students of the History Department of FIS UNP experienced culture shock, that they were surprised and unprepared for online learning. This research was raised to determine the factors and analysis of interest of FIS UNP History Department Students. This online learning system has both positive and negative impacts. The positive impact of the online learning system is that students have no difficulty in doing learning. They don't need to do activities to class just do it at home. While the negative impact of students who use telecomference will consume excess internet quota and adequate internet signal. The method used in this study is qualitative descriptive. This method is used to describe and expose the object to be studied in the form of analysis and make conclusions from the data. This has been reviewed from the distribution of questionnaires to students and descriptive analysis conducted by researchers. From the results, 60% of students of the History Department of FIS UNP have an interest and motivation in doing an online learning system rather than conventional learning.